MSC Therapies for COVID-19: Importance of Patient Coagulopathy, Thromboprophylaxis, Cell Product Quality and Mode of Delivery for Treatment Safety and Efficacy - Moll, Guido; Drzeniek, Norman; Kamhieh-Milz, Julian; Geissler, Sven; Volk, Hans-Dieter; Reinke, Petra (Frontiers in Immunology, 2020)
Numerous clinical trials of mesenchymal stromal/stem cells (MSCs) as a new treatment for coronavirus-induced disease (COVID-19) have been registered recently, most of them based on intravenous (IV) infusion. There is no approved effective therapy for COVID-19, but MSC therapies have shown first promise in the treatment of acute respiratory distress syndrome (ARDS) pneumonia, inflammation, and sepsis, which are among the leading causes of mortality in COVID-19 patients. Many of the critically ill COVID-19 patients are in a hypercoagulable procoagulant state and at high risk for disseminated intravascular coagulation, thromboembolism, and thrombotic multi-organ failure, another cause of high fatality. It is not yet clear whether IV infusion is a safe and effective route of MSC delivery in COVID-19, since MSC-based products express variable levels of highly procoagulant tissue factor (TF/CD142), compromising the cells' hemocompatibility and safety profile. Of concern, IV infusions of poorly characterized MSC products with unchecked (high) TF/CD142 expression could trigger blood clotting in COVID-19 and other vulnerable patient populations and further promote the risk for thromboembolism. In contrast, well-characterized products with robust manufacturing procedures and optimized modes of clinical delivery hold great promise for ameliorating COVID-19 by exerting their beneficial immunomodulatory effects, inducing tissue repair and organ protection. While the need for MSC therapy in COVID-19 is apparent, integrating both innate and adaptive immune compatibility testing into the current guidelines for cell, tissue, and organ transplantation is critical for safe and effective therapies. It is paramount to only use well-characterized, safe MSCs even in the most urgent and experimental treatments. We here propose three steps to mitigate the risk for these vulnerable patients: (1) updated clinical guidelines for cell and tissue transplantation, (2) updated minimal criteria for characterization of cellular therapeutics, and (3) updated cell therapy routines reflecting specific patient needs.